Don't kill the spider - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Helpful insects. spiders and pathogens Friends of the rice farmer / Shepard, B.M. et al.. (1987). Integrated Pest Management Foundation, International Rice Research Institute, Manila. Philippines 127 pp.